SOG’LOM OVQATLANISHDA AYRIM VITAMINLARNING AHAMIYATI - Xayrullayeva, Lobar; Avliyoqulova, Musharraf (MODERN PROBLEMS AND PROSPECTS FOR ORGANIZING A HEALTHY LIFESTYLE AND PROPER NUTRITION, 2024)
SOG’LOM OVQATLANISHDA AYRIM VITAMINLARNING AHAMIYATI